IMPLEMENTATION OF INCLUSIVE EDUCATIONAL CURRICULUM AT MIDDLE SCHOOL - Alfarisi, Muhammad Salman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education is an educational approach that aims to provide equal learning opportunities for all students, including students with special needs. This article aims to analyze the implementation of an inclusive education curriculum in secondary schools, focusing on the challenges, implementation strategies, and results achieved. This research uses qualitative methods with data collection techniques through interviews and observations in several secondary schools. The research results show that despite various challenges, implementing an inclusive curriculum can increase the engagement and academic achievement of students with special needs.